HUBUNGAN TINGKAT PENGETAHUAN TERHADAP PENGGUNAAN APLIKASI MOBILE JKN DI DESA SLOROK KECAMATAN KROMENGAN KABUPATEN MALANG - Andini Aulia Aghatsa (Program Studi Pendidikan Informatika, Universitas Citra Bangsa, 2023)
Mobile JKN is a form of BPJS Health's efforts to improve service quality. This application is expected to make it easier for participants to get administrative services without having to go to the branch office. Even though many residents of Slorok Village have become JKN participants, many still don’t know about the Mobile JKN application. The purpose of this study was to determine the relationship between the level of knowledge and the use of the Mobile JKN application in Slorok Village, Malang Regency. This study used a quantitative analytic research design and a survey research design with a cross sectional approach. The population is all residents of Slorok Village who are JKN participants using the purposive sampling technique of 98 respondents. The research instrument used a questionnaire and observation guidelines. Data analysis in this study used univariate and bivariate analysis. Bivariate analysis using the Chi-Square method. The results of this study were 68 respondents (69.39%) had less knowledge and 30 respondents (30.61%) had good knowledge about the Mobile JKN application. As many as 87 respondents (88.8%) didn’t use the Mobile JKN application and as many as 11 respondents (11.2%) used the application. The results of the Chi-Square Test obtained P-Value = 0.000 which is smaller than α = 0.05 so that is rejected and Hα is accepted. This shows that statistically there is a relationship between knowledge and the use of the Mobile JKN application in Slorok Village, Kromengan District, Malang Regency.